Funktionella aspekter på satsintonationen i svenska - Johansson, Iréne (Humanistiska fakulteten, 1978)
The present work is an investigation of the function of sentence intonation in Swedish for conveying information of various kinds: semantic-syntactic (distinguishing .declarative and interrogatory yes/no sentences) , stylistic (on the character of the speech situation), and dialectal information (on the regional background of the speakers). Finally the properties of the sentence intonation of individual speakers have been studied. The investigation is based on an acoustic analysis of recorded speech supplemented by other experiments involving perceptual tests in which specimens of natural speech, low pass filtered speech, and synthetic speech were presented to listeners. In the acoustic experiments five fundamental pitch parameters were investigated. The significance of these parameters for the listeners was tested in the perceptual experiments. The most evident difference between declarative and interrogatory intonation is in the marking of the frequency dominance manifested by certain properties of the features corresponding to the pitch parameters. The weak (negative) marking in declarative sentences implies a relatively low average and low peak value of pitch, an early position of the pitch peak in the sentence, and a relatively fast slope of the pitch. The contrasting strong (positive) marking in interrogatory sentences is characterized by the opposite properties. The marking of these features is in some cases optional. In speech delivered in situations when the pitch contour was one of very few or the only channel of information, e.g. in lists of read sentences, the intonation types are distinguished more clearly than when several channels were working, e.g. in spontaneous conversations. As far as dialectal information is concerned there is a tendency among speakers from the southern parts of Sweden to use a higher average level and greater variations of pitch than in Northern Sweden. In order to estimate the influence of particular vowels on the sentence intonation their inherent pitch was investigated. ...